Choose Yes or No to tell if each pair of expressions is equivalent. No 3x + 1 -x+1 and 4x + 1 4 Yes 2 + 6x and 2(3x + 1) No 3(x + 1) - (1 + x) and 2x + 3 Choose... 3x and 4(x + 1) = x - 4 2 Choose... 5.5 + 2.1+ 3.8x _ 4.1 and 1.4 + 5.9x

Choose Yes or No to tell if each pair of expressions is equivalent No 3x 1 x1 and 4x 1 4 Yes 2 6x and 23x 1 No 3x 1 1 x and 2x 3 Choose 3x and 4x 1 x 4 2 Choose class=

Respuesta :

We have the following:

The first

[tex]3x=4\cdot(x+1)-x-4[/tex]

resolving:

[tex]4\cdot(x+1)-x-4=4x+4-x-4=3x[/tex]

The answer is yes

The second:

[tex]5.5+2.1x+3.8x-4.1=1.4+5.9x[/tex]

resolving:

[tex]5.5+2.1x+3.8x-4.1=5.9x+1.4[/tex]

The answer is yes